Functional confectionary - Zyatyuk, Olga; Kondaurov, Konstantin (My University, 2012)
The functional confectionery segment is one with strong potential. Since the idea of adding ingredients with tangible benefits has already been brought to consumers' attention through functional foods in general, functional confectionery products do not require strong consumer education. Thus, the market is ripe for more innovative products.
Keywords: функціональні харчові продукти; гумка жувальна; шоколад; chewing gum; cocoa; chocolate; какао